Long-term prognosis of punctate inner choroidopathy lesions in pathologic myopia and their relationship to lacquer cracks - Kaori Sayanagi; Masaki Suzue; Satoko Fujimoto; So Goto; Chikako Hara; Yoko Fukushima; Kentaro Nishida; Kazuichi Maruyama; Shigeru Sato; Takatoshi Maeno; Kohji Nishida (Scientific Reports)
Abstract We investigated eyes with pathological myopic (PM) with punctate inner choroidopathy (PIC), a rare inflammatory disease, and focused on the association between PIC lesions and lacquer cracks (LCs). We retrospectively reviewed 36 myopic eyes diagnosed with PIC from 2001 to 2020 and followed for at least 3 years. Clinical characteristics were compared between the PM and non-PM eyes and between the PIC lesions with/without a coincident LC course. Factors associated with the final best-corrected visual acuity (BCVA) and PIC lesion area also were investigated. PM eyes were significantly older (p = 0.0440), had higher refractive error (p < 0.0001), a greater increase in the number of PIC lesions (p < 0.0001), poorer final BCVA (p = 0.0010), and more macular atrophy (p = 0.0252) than non-PM eyes. There were significant differences between PIC lesions with/without coincident LCs in age (p = 0.0034), refractive error (p = 0.0072), presence of PM (p < 0.0001), baseline and final BCVA (p = 0.0294 and p = 0.0373, respectively), and PIC lesion area % change/year (p = 0.0076). The final BCVA was associated with macular atrophy (p = 0.0006); the PIC lesion area % change/year was associated with a change in the number of PIC lesions (p = 0.0130) and whether they coincided with the LC course (p = 0.0491). PIC in PM eyes has a poor prognosis and could be subtyped according to the relationship with LCs or not.